WHY DID KOMPILASI HUKUM ISLAM SUCCEED WHILE ITS COUNTER LEGAL DRAFT FAILED? A Political Context and Legal Arguments of the Codification of Islamic Law for Religious Courts in Indonesia (JOURNAL OF INDONESIAN ISLAM, 2019)
Codification is a relatively new phenomenon in Islamic legal history. It intensified in the second half of the 20th Century with the adoption of modern nation state by Muslims which eventually replaced the judicial function of madhhab. Thus, fiqh must transform into state-sanctioned law to remain relevant, as it is also an avenue to apply Islamic law in Indonesian Religious courts. This article aims at unveiling the process of codification of three statutes of Islamic family law, but with different result. While KHI was successfully enacted, CLD KHI failed after facing fierce opposition from Muslim community. The different fate of these two statutes is at least due to two aspects; time and content. KHI was enacted in 1991 when president Soeharto was courting Muslim groups for political supports in his New Order authoritarian regime. Its content is somewhat mirroring the 1974 Marriage Law. Drafts of CLD-KHI was circulated in 2004 after the fall of Soeharto in which free speech is a norm. Content wise, CLD KHI featured liberal interpretation of Islamic family law or even departure from it which is prone to opposition from various Muslim groups.